Disinfection of Streptococcus mutans biofilm by a non-thermal atmospheric plasma brush. (14th June 2016) - Hong, Qing; Dong, Xiaoqing; Chen, Meng; Xu, Yuanxi; Sun, Hongmin; Hong, Liang; Wang, Yong; Yu, Qingsong
Abstract: This study investigated the argon plasma treatment effect on disinfecting dental biofilm by using an atmospheric pressure plasma brush. Streptococcus mutans biofilms were developed for 3 days on the surfaces of hydroxyapatite (HA) discs, which were used to simulate human tooth enamel. After plasma treatment, cell viability in the S. mutans biofilms was characterized by using 3-(4, 5-dimethylazol-2-yl)-2, 5-diphenyl-2 H -tetrazolium bromide (MTT) assay and confocal laser scanning microscopy (CLSM). Compared with the untreated control group, about 90% bacterial reduction in the biofilms was observed after 1 min plasma treatment. Scanning electron microscopy (SEM) examination indicated severe cell damages occurred on the top surface of the plasma treated biofilms. Confocal laser scanning microscopy (CLSM) showed that plasma treatment was effective as deep as 20 µm into the biofilms. When combined with antibiotic treatment using 0.2% chlorhexidine digluconate solution, the plasma treatment became more effective and over 96% bacterial reduction was observed with 1 min plasma treatment.